Iron-zinc-based composite material as well as preparation method and application thereof
By preparing iron-zinc-based composite materials with magnetic properties and high stability as photofenton catalysts, optimizing their synthesis and calcination conditions, the problem of low degradation efficiency of pollutants in the water system in the prior art is solved, and efficient dye degradation and Recycling of catalysts.
Patent Information
- Application Number
- CN202411251228.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2025-01-17
AI Technical Summary
The existing photofenton catalysts have poor effect on degrading pollutants in water system and are difficult to meet application requirements, especially the degradation efficiency of dye-based pollutants.
Using iron-zinc-based composite materials as heterogeneous photofenton catalyst, the iron-zinc-based group with magnetic properties is prepared by dissolving divalent zinc salt and trivalent iron salt in solvent, adjusting pH to alkaline, washing, drying and calcining. The composite material was subjected to photofenton degradation experiments under different conditions, and the catalyst synthesis system and calcination method were optimized to improve the degradation rate.
Under specific conditions, the degradation rate of the catalyst reaches more than 99%, which significantly improves the degradation effect of rhodamine B dye. Moreover, due to the magnetic properties, the catalyst is easy to recover and reuse, which improves the recycling value.
Smart Images

Figure CN119318963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts for treating water pollution, and in particular to an iron-zinc-based composite material and a preparation method and application thereof. Background Art
[0002] Dyes are complex in composition, most of which have stable molecular structures, large chromaticity, high salt content, good stability, slow degradation or even difficult to degrade, and cannot be cleaned up in sewage treatment plants using conventional biological, physical, and chemical methods, which have hazards such as damaging the ecological environment. Since dyes are easily soluble in water, they are widely used in the textile industry, food industry, and cosmetics industry, which can seriously endanger the health of animals, plants, and humans. Therefore, in order to more effectively solve the pollution of dye wastewater and achieve sustainable development, a green and efficient treatment method for dye pollution is urgently needed to solve the above problems. Among them, photo-Fenton technology has the characteristics of economy, environmental protection, and high efficiency, and is an effective solution for degrading water system pollution. Iron-zinc-based composite materials are heterogeneous photo-Fenton catalysts with the advantages of high stability, not easy to deteriorate, and response to visible light. They are also magnetic and can be recycled and reused, and are used in photo-Fenton catalysis for the degradation of various water system pollution. However, the effect of photo-Fenton catalysts in degrading water system pollution cannot meet its application requirements.
[0003] Therefore, it is necessary to prepare an iron-zinc-based composite material so as to have a better effect of degrading pollutants in water systems to solve the above problems. Summary of the invention
[0004] Based on the above, the object of the present invention is to provide an iron-zinc-based composite material which has excellent water system pollution degradation ability and is magnetic and recyclable.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing an iron-zinc based composite material comprises the following steps:
[0007] Dissolving a divalent zinc salt and a trivalent iron salt in a solvent, stirring, and obtaining a mixed solution;
[0008] Adjusting the pH of the mixed solution to alkaline to obtain a suspension;
[0009] The suspension is washed, filtered, dried and calcined to obtain an iron-zinc based composite material.
[0010] As a preferred embodiment of the method for preparing an iron-zinc-based composite material, in the mixed solution, the concentration of the trivalent iron salt is 40 mmol / L-200 mmol / L, and the molar ratio of the divalent zinc salt to the trivalent iron salt is 1:2.
[0011] As a preferred embodiment of the method for preparing an iron-zinc-based composite material, the divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol.
[0012] As a preferred solution of the method for preparing an iron-zinc-based composite material, when the divalent zinc salt and the trivalent iron salt are dissolved in a solvent, the stirring time is 10-60 minutes.
[0013] As a preferred solution of the method for preparing an iron-zinc-based composite material, the pH is adjusted to alkaline, with a pH value of 9-10.
[0014] As a preferred solution of the method for preparing the iron-zinc-based composite material, the drying temperature is 50-80°C.
[0015] As a preferred solution of the method for preparing an iron-zinc-based composite material, the calcination temperature is 600-800° C., and an inert atmosphere, preferably argon, is maintained during the calcination process.
[0016] An iron-zinc-based composite material is prepared by any one of the preparation methods described above.
[0017] A photo-Fenton catalyst comprises an iron-zinc-based composite material.
[0018] A catalytic method for a photo-Fenton catalyst performs photo-Fenton degradation under the conditions of different iron-zinc doping amounts, different synthesis systems of alcohol phase or water phase, and different calcination methods of air or argon.
[0019] The beneficial effects of the present invention are:
[0020] The present invention provides an iron-zinc-based composite material and a preparation method and application thereof. Since the iron-zinc-based composite material has the advantages of high stability, not easy to deteriorate, and responding to visible light, the photo-Fenton degradation performance of the catalyst is tested under the conditions of different iron-zinc doping amounts, different synthesis systems of alcohol phase or water phase, and different calcination methods of air or argon. It can be obtained that the degradation rate of the catalyst can reach more than 99% in 30min-60min. Among them, in the ethanol alkali system, when the concentration of the trivalent iron salt is 120mmol / L, the molar ratio of the divalent zinc salt and the trivalent iron salt is 1:2, and the degradation rate of the catalyst obtained by calcination in an argon atmosphere is the best. At pH=2, the catalyst input amount is 0.4g·L -1 , the amount of H2O2 was 48mM, and the degradation rate of 50mg·L -1 The degradation rate of Rhodamine B dye can reach more than 99%, and it has excellent water system pollution degradation performance. In addition, the iron-zinc-based composite material prepared by the invention has strong magnetism and is easy to be recycled and reused, which greatly improves its recycling value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0022] Figure 1 is a SEM image of the iron-zinc-based composite material prepared by the present invention, wherein a is Fe / Zn-1, b is Fe / Zn-2, c is Fe / Zn-3, d is Fe / Zn-7, e is Fe / Zn-4, and f is Fe / Zn-5;
[0023] Figure 2 is the XRD diagram of the iron-zinc-based composite material prepared by the present invention, wherein a is Fe / Zn-3, b is Fe / Zn-4, c is Fe2O3, and d is Fe / Zn-5;
[0024] Figure 3 is the RhB standard curve graph;
[0025] Figure 4 : is a performance diagram of photo-Fenton degradation of RhB by the iron-zinc-based composite materials with different zinc-iron doping amounts prepared by the present invention, wherein a is Fe / Zn-1, b is Fe / Zn-2, c is Fe / Zn-3, d is Fe / Zn-6, e is Fe / Zn-7, and f is Fe2O3;
[0026] Figure 5 It is a performance diagram of photo-Fenton degradation of RhB by the iron-zinc-based composite material prepared by the present invention in different preparation systems, wherein a is Fe / Zn-3, b is Fe / Zn-4, c is Fe / Zn-5, and d is ZnFe2O4;
[0027] Figure 6 1 is a performance diagram of photo-Fenton degradation of RhB by the iron-zinc-based composite material prepared by the present invention under different pH conditions, wherein a is pH=1, b is pH=2, and c is pH=3;
[0028] Figure 7 It is a performance diagram of photo-Fenton degradation of RhB by the iron-zinc-based composite material prepared by the present invention at different H2O2 dosages, wherein a is H2O2=16mM, b is H2O2=32mM, c is H2O2=48mM, and d is H2O2=64mM;
[0029] Figure 8The performance diagram of the photo-Fenton degradation of RhB by the Fe-Zn-based composite material prepared by the present invention at different catalyst dosages, wherein the catalyst concentration is 0.3 g·L -1 , b catalyst concentration is 0.4 g·L -1 , c catalyst concentration is 0.5 g·L -1 ;
[0030] Fig. 9 is the three-dimensional fluorescence spectrum of the iron-zinc-based composite material prepared by the present invention, wherein A is before adsorption, B is after adsorption, and C is after reaction;
[0031] Fig.10 This is a cyclic photo-Fenton degradation experimental diagram of the iron-zinc based composite material prepared by the present invention;
[0032] Fig.11 This is an optical photograph of the magnetic properties test of the iron-zinc-based composite material prepared by the present invention;
[0033] Fig.12 This is the result of the free radical capture photo-Fenton degradation of RhB experiment, where a is isopropanol, b is triethanolamine, c is p-benzoquinone, and d is Fe / Zn-3. DETAILED DESCRIPTION
[0034] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0035] The present invention will be further described below by means of specific examples.
[0036] This embodiment provides a method for preparing an iron-zinc based composite material, comprising the following steps:
[0037] S100: dissolving a divalent zinc salt and a trivalent iron salt in a solvent, stirring, and obtaining a mixed solution;
[0038] Specifically, the divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol. In the mixed solution, the concentration of the trivalent iron salt is 40mmol / L-200mmol / L, the molar ratio of zinc nitrate hexahydrate to ferric nitrate nonahydrate is 1:2, and specifically includes the concentration of ferric nitrate nonahydrate is 40mmol / L or 80mmol / L or 120mmol / L or 160mmol / L or 200mmol / L, preferably 120mmol / L, which is determined according to the actual situation; wherein the stirring time is 10-60min, which can be specifically set to 10min or 30min or 60min, which is determined according to the actual situation.
[0039] S200: adjusting the pH of the mixed solution to alkaline to obtain a suspension;
[0040] Specifically, the pH value of the solution was adjusted to 9-10 by adding 6 mol / L NaOH solution.
[0041] S300: washing, filtering, drying and calcining the suspension to obtain an iron-zinc based composite material.
[0042] Specifically, the drying temperature is 50-80°C, and the drying temperature can be specifically set to 50°C, 60°C or 80°C, preferably 60°C, which is determined according to actual conditions; the calcination temperature is 600-800°C, and can be specifically set to 600°C, 750°C or 800°C, preferably 750°C. During the calcination process, an inert atmosphere is maintained, preferably argon, which is determined according to actual conditions.
[0043] The present invention will be further described below by means of specific examples.
[0044] Example 1
[0045] A method for preparing an iron-zinc based composite material:
[0046] 50 mL of anhydrous ethanol was measured and placed in a 150 mL conical flask. 1 mmol of zinc nitrate hexahydrate and 2 mmol of ferric nitrate nonahydrate were weighed using a balance (the concentration of ferric nitrate nonahydrate was 40 mmol / L at this time), and the mixture was placed in the conical flask. The conical flask was placed on a magnetic stirrer, and the mixture in the flask was stirred for 30 min to obtain a uniform mixed solution containing zinc nitrate and ferric nitrate.
[0047] Then, the pH value of the solution was adjusted to 9-10 with 6 mol / L NaOH solution to obtain a brown-red suspension;
[0048] After washing and filtering the suspension, put it into an oven and dry it at 60°C for 12 hours. The obtained brown-red solid was calcined at 750°C in a tube furnace under an argon atmosphere and kept warm for 1 hour to generate an iron-zinc-based composite material. As shown in Table 1, in this embodiment, Zn(NO3)2 is 1 mmol, Fe(NO3)3 is 2 mmol, and the prepared iron-zinc-based composite material is named Fe / Zn-1.
[0049] Example 2
[0050] The preparation method and reaction conditions are consistent with those in Example 1, based on the addition of 50 mL of anhydrous ethanol, wherein Zn(NO3)2 is 2 mmol, Fe(NO3)3 is 4 mmol, and the concentration of Fe(NO3)3 is 80 mmol / L. The iron-zinc-based composite material prepared in this example is named Fe / Zn-2.
[0051] Example 3
[0052] The preparation method and reaction conditions are consistent with those of Example 1, based on the addition of 50 mL of anhydrous ethanol, wherein Zn(NO3)2 is 3 mmol, Fe(NO3)3 is 6 mmol, and the concentration of Fe(NO3)3 is 120 mmol / L. The iron-zinc-based composite material prepared in this example is named Fe / Zn-3.
[0053] Example 4
[0054] The preparation method and reaction conditions are consistent with those in Example 1, based on the addition of 50 mL of anhydrous ethanol, wherein Zn(NO3)2 is 4 mmol, Fe(NO3)3 is 8 mmol, and the concentration of Fe(NO3)3 is 160 mmol / L. The iron-zinc-based composite material prepared in this example is named Fe / Zn-6.
[0055] Example 5
[0056] The preparation method and reaction conditions are consistent with those of Example 1, based on the addition of 50 mL of anhydrous ethanol, wherein Zn(NO3)2 is 5 mmol, Fe(NO3)3 is 10 mmol, and the concentration of Fe(NO3)3 is 200 mmol / L. The iron-zinc-based composite material prepared in this example is named Fe / Zn-7.
[0057] In order to further illustrate the excellence of the present application, comparative examples 1-4 are added for illustration, as shown in Table 1, based on the addition of 50 mL of the reaction system, and other preparation methods and reaction conditions are consistent with those of Example 1.
[0058] Comparative Example 1 is Fe / Zn-4, wherein Zn(NO3)2 is 3mmol, Fe(NO3)3 is 6mmol, the reaction system is alcohol phase, and the calcination atmosphere is air;
[0059] Comparative Example 2 is Fe / Zn-5, wherein Zn(NO3)2 is 3 mmol, Fe(NO3)3 is 6 mmol, the reaction system is an aqueous phase, and the calcination atmosphere is argon;
[0060] Comparative Example 3 is Fe2O3, wherein Fe(NO3)3 is 8mmol;
[0061] Comparative Example 4 is ZnFe2O4, in which Zn(NO3)2 is 3 mmol, Fe(NO3)3 is 6 mmol, the reaction system is an aqueous phase and an alcohol phase, and the calcination atmosphere is air.
[0062] Table 1 Preparation formula of iron-zinc based composite materials with different zinc-iron doping amounts
[0063]
[0064] The morphology was observed using a scanning electron microscope. Figure 1 As shown in the figure, when the amount of zinc-iron substance is 1:2, the sample is rectangular, with an average diameter of about 280nm and a length of about 1μm. When the amount of zinc-iron substance increases to 2:4 and 3:6, the shape of the sample gradually shortens from rectangular to spherical, with a diameter of about 150-260nm, and the dispersion is relatively uniform. From d, it can be seen that as the amount of zinc-iron substance continues to increase, the spherical diameter of the sample also increases by about 400nm, and there is agglomeration phenomenon. Among them, e is a sample calcined under air atmosphere conditions with a zinc-iron substance amount of 3:6, which presents a slender ribbon morphology, with a wide side diameter of about 300nm, a narrow side diameter of about 100nm, and a length of about 1-1.5μm; f is a sample synthesized in a water system with a zinc-iron substance amount of 3:6, and its particles are evenly dispersed and the particle size distribution is uniform, about 50nm. In summary, the morphology and particle size of the samples obtained under different synthesis systems are different, which to a certain extent leads to different photo-Fenton degradation effects.
[0065] Using X-ray diffraction analysis, such as Figure 2As shown in the figure, the composite sample prepared in the alcohol-base system has characteristic diffraction peaks of ZnO at 31.6, 34.3, 36.1, 47.6, 56.7, and 62.4°, corresponding to the (100), (002), (101), (102), (110), and (103) crystal planes, respectively. In addition, peaks of Fe oxide appear at 20.0, 21.1, 29.8, 33.4, and 34.5°, which are basically consistent with the characteristic peaks of Fe2O3 (JCPD.No:40-1139). Compared with a and b, c only shows the characteristic diffraction peaks of Fe2O3 of the same crystal form. From d, it can be seen that the iron-zinc-based composite synthesized in the water system has characteristic peaks at 29.9, 35.3, 42.9, 53.2, 56.7, and 62.2°, corresponding to the (220), (311), (400), (420), (511), and (440) crystal planes of ZnFe2O4, respectively. This shows that the main components of the iron-zinc-based composite material synthesized in the alcohol-base system are metal oxides of the same crystal form regardless of whether it is calcined in an inert gas or in air, while the same formula in the water system is ZnFe2O4 crystals. Therefore, different synthesis systems produce different samples, resulting in different final photo-Fenton degradation efficiencies.
[0066] In order to further illustrate the application effect of the iron-zinc-based composite materials prepared in the above examples and comparative examples in photo-Fenton catalytic degradation, the following experiments were conducted.
[0067] 1. Drawing of the Rhodamine B standard curve
[0068] Weigh 1000 mg of RhB into a 500 mL beaker, add deionized water and stir with a glass rod until the RhB is completely dissolved. Then dilute the solution to a 1000 mL volumetric flask to prepare a concentration of 1000 mg·L -1 RhB solution. According to relevant literature, the maximum absorption wavelength of RhB is 554nm. Use a 1000μL pipette to transfer 0μL, 50μL, 100μL, 150μL, 200μL, and 250μL of the prepared RhB solution to a 50mL volumetric flask, then add deionized water to the volume and shake well. The concentration of the RhB solution is 0mg·L -1 , 1mg·L -1 , 2mg·L -1 , 3mg·L -1 , 4mg·L -1 , 5mg·L -1 Using deionized water as the substrate, the absorbance of RhB solutions of different concentrations at 554 nm was measured using a UV-visible spectrophotometer. With C0 as the horizontal axis and absorbance (Abs) as the vertical axis, a standard curve of RhB solution was drawn, as shown in Figure 2. Figure 3 shown.
[0069] The standard curve equation of RhB solution obtained by linear fitting is:
[0070] y=0.19509x+0.00462(R 2 =0.9998)
[0071] From the above formula, we can see that the linear fit is very high. In the concentration range of 0 mg·L -1 -5mg·L -1 The values are in a linear relationship, where the abscissa x represents the concentration of the RhB solution and the ordinate y represents the absorbance.
[0072] 2. Photo-Fenton degradation experiment
[0073] Measure 50mg·L -1 50mL of RhB (Rhodamine B) solution was placed in a 100mL double-layer jacket beaker, 0.05mL of concentrated hydrochloric acid was added to adjust the pH of the solution to 2, and 20mg of any one of the iron-zinc-based composite materials prepared in Examples 1-5 was added, and placed in a visible light multiphase photocatalytic reactor, the light source was a 500W xenon lamp, and the temperature was maintained at 20°C using a water circulation system. After stirring with a magnetic stirrer for half an hour under dark conditions, the system reached adsorption-desorption equilibrium. 2mL of the suspension was taken with a 5mL syringe and filtered with a 0.45μm polyethersulfone filter membrane (PES), and its absorbance was measured with a UV-visible spectrophotometer. After that, 0.1mL of 30% H2O2 solution (32mM) was added to the RhB solution, and the visible light was turned on at the same time, and the photo-Fenton reaction was started under the xenon lamp light source. The suspension was taken at 10min, 20min, 30min, 40min, 50min, and 60min, filtered with 0.45μm PES, and the absorbance of the solution was measured at the maximum absorption wavelength of 554nm. The concentration of RhB after filtration was calculated by substituting it into the standard curve equation of RhB. The catalytic effect of RhB degradation is expressed by the removal rate η, and the calculation equation is as follows:
[0074]
[0075] Where C0 is the initial concentration of RhB solution, in mg·L -1 ; C t is the concentration of RhB solution at the end of the experiment, in mg·L -1 .
[0076] 3. Photo-Fenton degradation performance of iron-zinc based composites with different zinc and iron doping amounts
[0077] In order to achieve the best photo-Fenton reaction performance, the relationship between the Fe-Zn-based composites with different Zn-Fe doping amounts and the degradation rate was explored. Figure 4As shown, all degradation characteristics conform to pseudo-first-order kinetics, ln(C0 / C)=kt, where C0 is the initial concentration of RhB solution, C is the concentration of RhB solution at t (min), and k is the first-order rate constant.
[0078] from Figure 4 It can be seen that the rate constants of the iron-zinc-based composite material Fe / Zn-3 are 1.23, 1.43, 1.06, 1.96, and 1.77 times those of Fe / Zn-1, Fe / Zn-2, Fe / Zn-6, Fe / Zn-7, and Fe2O3, respectively. It can be seen that with the increase in the amount of zinc salt and iron salt, the degradation rate of RhB first increases and then decreases. When the amount of zinc salt and iron salt is 3:6, the catalytic degradation effect of Fe / Zn-3 prepared in Example 1 is the best, and the degradation rate is 99.2% at 30 minutes. When the ratio of zinc salt to iron salt reaches 5:10, the degradation rate of RhB decreases rapidly. This phenomenon may be due to the excessive content of iron and zinc salts, which causes the catalyst to agglomerate and affects the photo-Fenton activity. In contrast, the photo-Fenton degradation rate of Fe2O3 only reached 81.2% at 30 min, which is much lower than the degradation rate of Fe / Zn-3. This is because the two substances Fe2O3 and ZnO in Fe / Zn-3 form a heterojunction, which improves the transfer efficiency of photogenerated electrons, and thus its photo-Fenton degradation rate also increases accordingly.
[0079] 4. Photo-Fenton degradation performance of Fe-Zn-based composites with different preparation systems
[0080] In order to achieve the best photo-Fenton reaction performance, the relationship between the preparation conditions and degradation rate of different Fe-Zn-based composites was explored. Figure 5 As shown in the figure, all degradation characteristics conform to pseudo-first-order kinetics, and the rate constants of Fe / Zn-3 are 1.23, 1.57, and 1.36 times those of Fe / Zn-4, Fe / Zn-5, and ZnFe2O4, respectively. This indicates that under the reaction conditions and calcination methods of different solvents, the degradation rate of RhB by the iron-zinc-based composite material calcined with anhydrous ethanol as the solvent and argon as the protective gas is the highest. The photo-Fenton degradation rates of the catalysts synthesized in the water system (such as c), or calcined in the air (such as b), and the catalysts synthesized by hydrothermal synthesis reported in the literature (such as d) are much lower than the degradation efficiency of the Fe / Zn-3 catalyst. This may be because the alkaline solution of ethanol has a certain synergistic effect on the hydrolysis of iron-zinc metal salts during the preparation process, so that the catalyst has more active sites to contact with the light source and RhB pollutant molecules, thereby enhancing the photo-Fenton performance.
[0081] 5. Effects of other factors on the performance of photo-Fenton degradation of RhB solution by Fe-Zn-based composite materials (refer to the experimental process of photo-Fenton degradation experiment)
[0082] (1) Photo-Fenton degradation of RhB at different pH values
[0083] Measure 50mg·L -1 50 mL of RhB solution was put into a 100 mL double-layer jacketed beaker. The input amount of the iron-zinc-based composite material prepared in Example 1 was 0.4 g·L -1 , the amount of H2O2 was 32 mM, and the pH of the solution was 1, 2, and 3. The other steps were consistent with the photo-Fenton degradation experiment.
[0084] The results of the study on the effect of pH value are as follows Figure 6 As shown in the figure, in the solution with pH value of 1 and 2, the removal rate of RhB in 30min was greater than 99% and even reached 100%, while when the pH value was 3, the removal rate of RhB in 30min was only 23%. This shows that although the applicable pH range of iron-zinc-based composite materials is relatively narrow, they have extremely high catalytic degradation activity in a specific pH range. At lower pH values, it may be due to the increase of iron ions dissolved in the solution, so that the concentration of iron ions in the solution increases, which is conducive to the reaction with H2O2 to generate rich H + to oxidatively degrade RhB. As the pH value increases, more OH - Will occupy Fe 3+ The reaction sites of Fe 3+ The interaction between RhB and H2O2 will be inhibited, resulting in a decrease in the photo-Fenton degradation of RhB. Therefore, the degradation effect is best when the pH value is 2.
[0085] (2) H2O2 photo-Fenton degradation of RhB
[0086] Measure 50mg·L -1 50 mL of RhB solution was put into a 100 mL double-layer jacketed beaker. The input amount of the iron-zinc-based composite material prepared in Example 1 was 0.4 g·L -1 The pH of the solution was 2, and the amounts of H2O2 were 16 mM, 32 mM, 48 mM, and 64 mM, respectively. The other steps were consistent with the photo-Fenton degradation experiment.
[0087] Photo-Fenton degradation effects under different H2O2 concentrations Figure 7As shown in the figure, in the photo-Fenton catalytic degradation system of iron-zinc composite materials, the reduction of H2O2 by the catalyst and the decomposition of H2O2 itself can produce hydroxyl radicals (·OH), so within a certain range, the amount of free radicals ·OH generated is proportional to the concentration of H2O2. When the amount of H2O2 added increased from 16mM to 48mM, the removal rate of RhB increased from 96.4% to 99.2% at 30min, which indicates that the activated H2O2 under photocatalysis produced more active substances ·OH, which directly accelerated the degradation rate of the experimental reaction. However, when the concentration of H2O2 increased to 64mM, the degradation rate did not increase compared to 48mM. This phenomenon may be due to the capture of free radicals ·OH by excessive H2O2. The degradation rate of RhB reached 99.8% at 40min. Therefore, the degradation effect was best when the amount of H2O2 was 48mM.
[0088] (3) Effect of catalyst dosage on photo-Fenton degradation of RhB
[0089] Measure 50mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The pH of the solution was 2. The amount of H2O2 was 48 mM. The input amounts of the iron-zinc-based composite material prepared in Example 1 were 0.3 g·L -1 , 0.4g·L -1 , 0.5g·L -1 The other steps were consistent with the photo-Fenton degradation experiment.
[0090] Effect of catalyst dosage on photo-Fenton degradation of RhB Figure 8 As shown in the figure, when the amount of catalyst increases from 0.3 g·L -1 Increased to 0.4 g·L -1 , the degradation rate of RhB increased from 97.7% to 99.2% at 30 min. This is because the increase in the amount of catalyst provides more adsorption and catalytic active sites, which has a positive effect on the reaction rate. When the catalyst concentration is then increased to 0.5 g·L -1 When the catalyst concentration was high, the removal rate of RhB decreased instead of increasing, indicating that the high concentration of catalyst would inhibit the rapid degradation of RhB by the Fe-Zn-based composite material. The reason for this phenomenon may be that when the Fe-Zn-based composite material catalyst mass is small, the photogenerated electron-hole (h + ) is produced in small amounts, so the catalytic degradation performance is not high. As the amount of catalyst increases, h + The number of photo-Fenton will also increase, and the photo-Fenton performance will gradually improve. + At this point, increasing the amount of catalyst will not only fail to improve the efficiency of photo-Fenton, but too much catalyst will block the contact area between light and pollutants in the solution, which will affect the photo-generated+ The generation of photo-Fenton efficiency is reduced. Therefore, the amount of catalyst used is 0.4 g·L -1 The degradation effect is best.
[0091] 5. Three-dimensional fluorescence detection
[0092] The degradation process of RhB by the iron-zinc-based composite material prepared in Example 1 was detected by three-dimensional fluorescence technology. Fig. 9 As shown in Figure A, peak a at 560-610 / 570-670nm, peak b at 460-540 / 610-660nm, and peak c at 235-380 / 580-610nm are the three characteristic fluorescence peaks of RhB. As the dark reaction proceeds, after 30 minutes (Figure B), the centers of peak a, peak b, and peak c did not move significantly, indicating that the adsorption effect of the catalyst was general. In addition, as the photo-Fenton reaction proceeds, peaks a, b, and c all disappear after 60 minutes of reaction (Figure C), indicating that the RhB molecules have been completely decomposed into small inorganic salt molecules.
[0093] 6. Cycle test
[0094] The fixed experimental reaction conditions are: the input amount of the iron-zinc-based composite material prepared in Example 1 is 0.4 g·L -1 The pH of the solution was 2, and the amount of H2O2 was 48 mM. According to the experimental method of photo-Fenton catalysis, no liquid was taken during the reaction. After the reaction was completed, the solution was poured into a beaker, and the remaining catalyst was adsorbed to the bottom wall of the beaker with a magnet. The upper clear liquid was poured out, and the remaining iron-zinc-based composite material raw materials were washed three times with deionized water, and then 50 mL 50 mg·L of the same concentration was added again. -1 The RhB solution was added and the next catalytic degradation experiment was started. The same experimental steps were repeated 5 times.
[0095] like Fig.10 As shown in the figure, the catalytic degradation efficiency of the iron-zinc-based composite catalyst for RhB can still be as high as 99% after repeated cycles for 5 times, which confirms that the stability of the Zn and Fe active components in the catalyst is conducive to the reuse of the iron-zinc-based composite catalyst. In addition, since the iron-zinc-based composite catalyst is magnetic, the raw materials can be relatively easily separated from the solution and recycled by applying an external magnetic field for further recycling.
[0096] 7. Magnetic performance test
[0097] Depend on Fig.11As shown in the figure, the iron-zinc-based composite materials prepared by different systems are all brown-red solid powders, which can move in a directional manner under an external magnetic field. Even if the powder is inverted, it is completely attracted by the magnet, which proves that the prepared iron-zinc-based composite materials have strong magnetic response performance. This feature is conducive to the recycling of experimental materials in degraded wastewater, greatly improving its recycling value.
[0098] 8. Photo-Fenton degradation mechanism
[0099] Measure 50mg·L -1 50 mL of RhB solution was placed in a 100 mL double-layer jacketed beaker. The pH of the solution was 2, the amount of H2O2 was 48 mM, and the amount of the iron-zinc-based composite material prepared in Example 1 was 0.4 g·L -1 , and 0.5mmol isopropanol (IPA), 0.5mmol triethanolamine (TEA), and 0.05mmol p-benzoquinone (BQ) were added as ·OH, h + 、O2 - The other steps are consistent with the photo-Fenton degradation experiment. In the experimental reaction system of photo-Fenton catalytic degradation of RhB by Fe-Zn-based composite materials, a series of free radical scavengers are added to carry out free radical scavenging experiments to determine the active species.
[0100] The experimental results are as follows Fig.12 Isopropyl alcohol (IPA), triethanolamine (TEA), and p-benzoquinone (BQ) were used as the capture agents for hydroxyl radicals (·OH) and photogenerated holes (h + ), superoxide radicals (·O2 - ) capture agent, after 30 minutes of light reaction, the photo-Fenton catalytic degradation rate of RhB by the iron-zinc-based composite material was 99.2%. After adding triethanolamine (TEA), the photo-Fenton catalytic degradation rate of RhB dropped sharply to 18%. This shows that triethanolamine (TEA) captures photogenerated holes (h + ) free radicals and significantly reduced the catalytic degradation ability of the catalyst. When isopropyl alcohol (IPA) and para-benzoquinone (BQ) were added, the photo-Fenton catalytic degradation rate of RhB dropped to 85% and 98%, respectively, and the degradation effect was not significantly weakened. The results show that in the photo-Fenton catalytic degradation experiment of RhB on Fe-Zn-based composite materials, photogenerated holes (h + ) is the main active species in the photo-Fenton reaction system.
[0101] In summary, through the above experiments, it can be obtained that the iron-zinc-based composite material prepared in Example 3, in the ethanol alkali system, based on the addition of 50 mL of anhydrous ethanol, the zinc-iron molar ratio is 3 mmol:6 mmol, and the degradation rate of the catalyst obtained by calcining under an argon atmosphere reaches more than 99% at 30 minutes.
[0102] At 50mg·L -1 RhB was the target pollutant, and the effects of different pH, different H2O2 concentrations, and different amounts of catalyst on the photo-Fenton degradation ability of Fe-Zn-based composite materials were investigated. The results showed that the optimal degradation conditions were: pH = 2, H2O2 dosage of 48mM, and catalyst dosage of 0.4g·L -1 When the pollution is degraded, the ability is best.
[0103] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing an iron-zinc based composite material, characterized in that: The following steps are involved: Dissolving a divalent zinc salt and a trivalent iron salt in a solvent, stirring, and obtaining a mixed solution; Adjusting the pH of the mixed solution to alkaline to obtain a suspension; The suspension is washed, filtered, dried and calcined to obtain an iron-zinc based composite material.
2. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: In the mixed solution, the concentration of the trivalent iron salt is 40mmol / L-200mmol / L, and the molar ratio of the divalent zinc salt to the trivalent iron salt is 1:
2.
3. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: The divalent zinc salt includes zinc nitrate hexahydrate, the trivalent iron salt includes ferric nitrate nonahydrate, and the solvent includes anhydrous ethanol.
4. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: When the divalent zinc salt and the trivalent iron salt are dissolved in the solvent, the stirring time is 10-60 minutes.
5. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: The pH is adjusted to alkaline, with a pH value of 9-10.
6. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: The drying temperature is 50-80°C.
7. The method for preparing the iron-zinc based composite material according to claim 1, characterized in that: The calcination temperature is 600-800° C., and an inert atmosphere is maintained during the calcination process.
8. An iron-zinc based composite material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.
9. A photo-Fenton catalyst, characterized in that: Including the iron-zinc based composite material as described in claim 8.
10. The catalytic method of photo-Fenton catalyst according to claim 9, characterized in that: Photo-Fenton degradation was carried out under the conditions of different Fe-Zn doping amounts, different synthesis systems in alcohol phase or water phase, and different calcination methods in air or argon.